Predictors of each quality of life dimension in Crohn's disease patients initiating an anti-TNF treatment: differentiated effects of patient-, disease-, and treatment-related characteristics. (4th May 2022) - Monmousseau, Fanny; Mulot, Lucile; Rusch, Emmanuel; Picon, Laurence; Laharie, David; Fotsing, Ginette; Gargot, Dany; Charpentier, Cloé; Buisson, Anthony; Trang-Poisson, Caroline; Dib, Nina; DES Garets, Véronique; et al.
Abstract: Background and aims: In Crohn's disease (CD), a composite therapeutic target was recently recommended, including both objective measurement (endoscopic remission) and Patient-Reported Outcomes (resolution of abdominal pain and normalization of bowel function). All dimensions of health-related quality of life (HRQoL) are impacted: not only bowel symptoms but also systemic symptoms, emotional wellbeing and social function. Thus, understanding the predictors of each HRQoL dimension would improve patient management. However, analysis of these factors has only been found in a few publications, with some limitations. Therefore, this study aimed to explore the evolution of the HRQoL of CD patients during six months after initiation of anti-TNF and to identify its predictors. Methods: We analyzed data of 56 patients included in a multicenter prospective cohort study (COQC-PIT). HRQoL measures (using IBDQ-32) and data related to patient, disease and treatment characteristics were collected every two months. Generalized estimating equations were used. Results: Overall HRQoL was significantly improved 2 months after anti-TNF initiation, and then stagnated. Patient, disease, and treatment characteristics have differentiated impacts on the overall score and on each dimension of quality of life. Subcutaneous anti-TNF had no significant effect on overall HRQoL, improving only emotional function and bowel symptoms. Concomitant use of corticosteroids and/or immunomodulators impaired almost all dimensions. Having children or working altered bowel symptoms. Disease duration and active smoking negatively impact emotional function and systemic symptoms. Conclusions: Each HRQoL dimension, not only bowel symptoms, and their influencing factors should therefore be considered in medical decision-making, especially in months following the initiation of a new treatment such as anti-TNF.